Crystallization‐Induced Reversal from Dark to Bright Excited States for Construction of Solid‐Emission‐Tunable Squaraines. Issue 25 (23rd January 2020) - Yang, Shuaijun; Yin, Ping‐An; Li, Lin; Peng, Qian; Gu, Xinggui; Gao, Ge; You, Jingsong; Tang, Ben Zhong
Abstract: Squaraines (SQs) with tunable emission in the solid state is of great importance for various demands; however a remaining challenge is emission quenching upon aggregation. Herein, a unique SQ, named as CIEE‐SQ, is designed to exhibit strong emission in crystal, undergoing crystallization‐induced reverse from dark 1 (n+σ, π*) to bright 1 (π, π*) excited states. Such an excited state of CIEE‐SQ can be subtly tuned by molecular conformation changes during the unexpected temperature‐triggered single‐crystal to single‐crystal (SCSC) reversible transformation. Furthermore, co‐crystallization between CIEE‐SQ and chloroform largely stabilize the 1 (π, π*) state, enhancing the transition dipole moment and decreasing the reorganization energy to boost the fluorescence, which is promising in data encryption and decryption. Abstract : A unique squaraine, CIEE‐SQ, exhibits strong emission in the crystal, undergoing crystallization‐induced reversal from dark 1 (n+σ, π*) to bright 1 (π, π*) excited states. Such an excited state can be tuned by an unexpected temperature‐triggered single‐crystal to single‐crystal reversible transformation. Co‐crystallization between CIEE‐SQ and chloroform largely boosts the fluorescence.